National Gallery of Art, Washington - Walker, John, 1906-1995; Brown, J. Carter (John Carter), 1934-2002 (New York : Harry N. Abrams, 1975)
Contiene más de 1,000 fotografías de pinturas con texto de la Galería Nacional de Arte.
Foreword / By J. Carter Brown -- The National Gallery of Art -- Genesis -- The Founding benefactors -- Policies -- Activities -- Conclusion -- The Plates: Italian schools: XIII through early XVI century -- Northern schools: XV and XVI century -- Italian schools: XVI and XVII century -- Spanish school: XVI and XVII century -- Flemish and Dutch schools: XVII century -- French and Italian schools: XVII and XVIII century -- British and American schools: XVIII century -- Spanish and British schools: XIX century -- French school: XIX century -- American school: XIX and early XX century -- XX century -- Sculpture -- Drawings.
Donación de la Colección de Eduardo Diez Morales.
Incluye índice.
Keywords: GALERIA NACIONAL DE ARTE (WASHINGTON, ESTADOS UNIDOS); GALERIAS DE ARTE -- WASHINGTON; ARTE ESTADOUNIDENSE